(untitled) (Bangladesh Journal of Medical Science, 2015)
Ageing is an inevitable life process characterized by a gradual functional decline of all organ systems occurring at the cellular, tissue, organ and whole body levels further leading to the development of diseases and finally death. Although aging is a normal physiological process, it can be accelerated during oxidative stress or during chronic inflammatory conditions. An appropriate theory must explain four main characteristics of ageing: it is endogenous, progressive, irreversible and deleterious for the individual. Oxidative stress is caused by imbalance between oxidants and antioxidants. Reactive Oxygen Species (ROS) not only cause cell damage, but are also involved in intracellular signaling. ROS include superoxide (O2-), hydrogen peroxide (H2O2), hydroxyl radical (OH-) and peroxynitrite. Various enzyme systems produce ROS including the mitochondrial electron transport chain, cytochrome P450, lipoxygenase, cyclooxygenase, the NADPH oxidase complex, xanthine oxidase and peroxisomes. More research is needed to explain the exact mechanisms related to ageing and oxidative stress. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.221-227